Invisible mobilities: stigma, immobilities, and female sex workers' mundane socio-legal negotiations of Dhaka's urban space. Issue 4 (3rd July 2020) - Shewly, Hosna J.; Nencel, Lorraine; Bal, Ellen; Sinha-Kerkhoff, Kathinka
ABSTRACT: Drawing on ethnography, this paper conceptualizes invisible mobilities by exploring the linkages between mobility, invisibility and hotel and residence based sex work in Dhaka, Bangladesh. Since both are illegal in Bangladesh, hotel and residence based sex workers (HRSWs) become targets of the different laws and sex work related social stigma. We show, in this paper, how invisible mobilities is used to strategize and counter-enact against the existing exploitative gendered socio-political-legal regimes and practices involved in sex work. Invisible mobilities refers to the way HRSWs move in order to hide their occupation from society and the law. Invisibility is at the core of all these connections: It enables HRSWs to continue sex work and avoid exclusion from family and members of their communities. While making themselves invisible permits them to continue their daily ways to earn a living, it also reinforces the same social stigma they are constantly trying to avoid. In doing so, this paper reveals the political economy of sex work in the city and provides a new theoretical window to understand the connections between gender, mobility and the city, constructing a bridge between mobility and sex work studies literature.